2023
DOI: 10.1002/jbio.202300016
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy in chronic heart failure diagnosis based on human skin analysis

Abstract: This work aims at studying Raman spectroscopy in combination with chemometrics as an alternative fast noninvasive method to detect chronic heart failure (CHF) cases. Optical analysis is focused on the changes in the spectral features associated with the biochemical composition changes of skin tissues. A portable spectroscopy setup with the 785 nm excitation wavelength was used to record skin Raman features. In this in vivo study, 127 patients and 57 healthy volunteers were involved in measuring skin spectral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Aiming at checking the performance of the built models on the new data, we considered splitting the data in two sets used for training and validation, respectively, with the main goal to compare the discrimination accuracy features on these two sets [71,72]. In this sense, the data were separated in two sets, denoted map 1 and map 2.…”
Section: Multivariate Analysis Of Normalized Datamentioning
confidence: 99%
“…Aiming at checking the performance of the built models on the new data, we considered splitting the data in two sets used for training and validation, respectively, with the main goal to compare the discrimination accuracy features on these two sets [71,72]. In this sense, the data were separated in two sets, denoted map 1 and map 2.…”
Section: Multivariate Analysis Of Normalized Datamentioning
confidence: 99%
“…In this context, Raman spectroscopy can have greater potential in comparison to the laboratory procedures currently utilized in clinical settings. On the other hand, several studies [30,38] have reported that Raman spectral features analyzed with different mathematical methods (chemometrics, machine learning, artificial intelligence, etc.) are able to detect a disease by means of the meaningful spectral differences between the disease and control cases without identifying the exact biomarkers.…”
Section: Introductionmentioning
confidence: 99%